Light‐Activated Rapid Disinfection by Accelerated Charge Transfer in Red Phosphorus/ZnO Heterointerface. Issue 3 (8th February 2019) - Li, Jun; Liu, Xiangmei; Tan, Lei; Liang, Yanqin; Cui, Zhenduo; Yang, Xianjin; Zhu, Shengli; Li, Zhaoyang; Zheng, Yufeng; Yeung, Kelvin Wai Kwok; Wang, Xianbao; Wu, Shuilin
Abstract: A red phosphorus (RP)/ZnO heterojunction thin film is developed to harvest solar or light emitting diode (LED) light for rapid, effective, ecofriendly, lower‐cost, and safe disinfection, which is convenient for universal and large‐scale deposition. The most stable geometrical structure of the RP/ZnO heterojunction, i.e., an RP (001) plane and a ZnO (002) plane, exhibits charge redistribution largely at the interface region. Therefore, the effective interfacial charge transfer and the improved separation efficiency of photogenerated electron–hole pairs can strongly boost reactive oxygen species (ROS)‐generation reactions to enhance photocatalytic bacterial inactivation. The excellent light‐activated point‐of use disinfection can be achieved even through LED light of phone. Additionally, the RP/ZnO heterojunction also possesses excellent solar light‐to‐heat conversion efficiency, leading to further lethality to bacteria through hyperthermia. Antibacterial efficacy of 99.96 ± 0.03% against Staphylococcus aureus at 5 min and 99.97 ± 0.02% against Escherichia coli at 4 min can be attributed to the synergetic antibacterial activity of solar photocatalysis and photothermal effect (more than 50 °C in 2 min). This platform provides a surface strategy for designing synergetic photocatalytic and photothermal materials to fully harvest solar energy for not only water disinfection but also antibacterial surfaces in medical facilities, touch screen devices, or seawater desalination. Abstract : A red phosphorus (RP)/ZnO heterojunction thin film is developed to harvest solar or light emitting diode (LED) light for rapid, effective, eco‐friendly, lower‐cost and safe disinfection by its photocatalysis and photothermal effect. Light‐activated ultrafast bacterial inactivation can be attributed to the synergetic ROS and heat by RP/ZnO heterojunction.